ERDOĞAN VERSUS GÜLEN: Perebutan Pengaruh antara Islam Politik Post-Islamis dengan Islam Kultural Apolitis - Akhmad Rizqon Khamami (AL-TAHRIR, 2016)
Abstract: This article is aimed at disclosing a conflict of military coup attempt in Turkey occurring on July 15, 2016. The research question addressed in this article is why Fethullah Gülen was to blame in the military coup. It was clearly read that military coups happening in the story was as a personal feud between Recep Tayyip Erdoğan and Fethullah Gülen. To obtain an overall picture of the dispute in the coup attempt, the author presents three conflicting groups: secularists, Islamist or ultranationalist elites and moderate Muslim called cemaat. Military represents a secular group, Erdoğan represents Islamist or ultranationalist elites, while Gülen represents moderate Muslim pro-Western brand of Sunni Islam. The conflict between the Gülen and Erdoğan was actually triggered to get more influence in the Turkish national political stage. The author noted that this personal conflict was really a feud between the both two men from different groups of Muslims having different perspective though really both of them coming from one religion (Islam) and one stream sect (Sunni). Gülen had struggled through a political cultural lines, while Erdoğan had fought through political channels post-Islamism. ملخص: يتناول هذا البحث النزاع المحتدم حول محاولة الانقلاب العسكري الذي حدث في تركيا 15 يوليو 2016. ويحاول هذا البحث الإجابة على سؤال واحد مفاده : لماذا تشير أصابع الاتهام إلى فتح الله كولن ويلقى اللوم عليه؟ من الملحوظ جليا أن الانقلاب العسكري في هذه المرة تعكس نزاعا فرديا بين رجب طيب إردوغان وفتح الله كولن. وتجلية للصورة الحقيقية  من هذا النزاع، يتناول الباحث ثلاث فئات لكلٍّ منها دورها في هذه المحاولة الانقلابية: فئة علمانية تتمثل في العسكرية التركية، وفئة إسلامية سياسية تتمثل في حزب رجب طيب إردوغان، وفئة إسلامية ثقافية تحت قيادة فتح الله كولن. فالنزاع المحتدم بين كولن وإردوغان في الحقيقة هو من جرّاء تنافسهما في استجلاب الهيمنة على المسرح السياسي في الدولة. ويرى الباحث أن هذا النزاع الفردي يعود إلى نزاع بين مسلمين يمثلان تيارين إسلاميين مختلفين في منهجية النظر، مع أنهما ينتميان إلى دين واحد (الإسلام) وينبثقان من مذهب واحد (المذهب السني). فكولن يختار المسار الثقافي اللاسياسي، بينما يفضّل إردوغان المسلك السياسي على منوال ما بعد الإسلاموية. Abstrak: Artikel ini mengupas konflik di seputar kudeta militer di Turki yang terjadi pada tanggal 15 Juli 2016. Pertanyaan riset yang dibahas dalam artikel ini adalah mengapa dalam kudeta militer tersebut justru Fethullah Gülen yang disalahkan? Terbaca dengan jelas bahwa kudeta militer kali ini bercerita tentang perseteruan personal antara Recep Tayyip Erdoğan dengan Fethullah Gülen. Untuk memperoleh gambaran utuh mengenai perseteruan ini penulis menghadirkan tiga kelompok yang berkonflik dalam drama kudeta tersebut: kelompok sekuler, Islam politik dan Islam kultural. Militer mewakili kelompok sekuler. Erdoğan mewakili Islam politik, sedangkan Gülen mewakili Islam kultural. Konflik antara Gülen dengan Erdoğan sesungguhnya dipicu oleh perebutan pengaruh di panggung nasional Turki. Penulis melihat bahwa konflik personal ini tidak lain adalah perseteruan antara dua sosok Muslim dan sekaligus dua kelompok Islam yang berbeda dalam cara pandang meskipun sama-sama berasal dari satu agama (Islam) dan satu aliran (Sunni). Gülen berjuang lewat jalur kultural apolitis, sedangkan Erdoğan berjuang melalui jalur politik post-Islamisme.